Monocyte-derived extracellular trap (MET) formation induces aggregation and affects motility of human spermatozoa in vitro. (3rd September 2019) - Schulz, Mabel; Zambrano, Fabiola; Schuppe, Hans-Christian; Wagenlehner, Florian; Taubert, Anja; Gaertner, Ulrich; Sánchez, Rául; Hermosilla, Carlos
ABSTRACT: The presence of bacteria and/or leukocytes can alter semen quality resulting in low sperm quality and infertility. Inflammation or infection increases the numbers of PMN or macrophages/monocytes in male genital tract. Release of extracellular traps (ETs) by leukocytes has been recognized as a novel mechanism of early host innate immunity, in response to invasive pathogens. This is the first work that evaluated the mechanism of triggered ETs in monocytes co-incubated with spermatozoa or bacteria and the effect on sperm function. Selected spermatozoa and human monocytes isolated from peripheral blood were obtained by healthy donors. Two experimental models were developed, one aseptic (non-infectious) incubating spermatozoa and monocytes, and septic models (infectious) incubating spermatozoa with monocytes and uropathogenic Escherichia coli ( E. coli ). ETs of monocytes (METs) (DNA, global histone and citrullinated histones) were visualized by scanning electron microscopy (SEM) and immunofluorescence analyses. Progressive motility was performed at 0, 10, 30, 60, and 180 min after co-incubation with CASA system. SEM- and immunofluorescence-analyses revealed human spermatozoa alone or in the presence of E. coli as strong inducers METs. In aseptic model, the motility decreased to 65.2 ± 3.5% at 10 min of incubation and 29.3 ± 3.3% at 30 min (p < 0.001). In septic model, motility decreased to 44.5 ± 5.9% (10 min) and 12.7 ± 2.2% (30 min) (p < 0.001). MET-derived small spermatozoa aggregations were observed in both models. METs might physically block spermatozoa and decrease motility after a brief contact. This may impair male fertility, especially in patients with genital tract infections or chronic inflammation. Abbreviations : PMN: polymorphonuclear; ETs: extracellular traps; E. coli: Escherichia coli ; METs: ETs of monocytes; SEM: scanning electron microscopy; NE: neutrophil elastase; MPO: myeloperoxidase; MAGI: male accessory gland infection; PBMC: peripheral blood mononuclear cells; RT: room temperature; CFU: colony forming units; CASA: computer-aided sperm analysis; H4Cit3: histone H4 citrullinated 3